INTERROGATIVE SENTENCES IN TOBA BATAK LANGUAGE FROM A LINGUISTIC TYPOLOGY PERSPECTIVE: AN ANALYSIS BASED ON COMRIE AND PAYNE - Ida Basaria; Marniman Jemila Zalukhu; Divya Neila Bulanda Sari; Tamba, Grace (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to describe the forms, functions, and typological characteristics of interrogative constructions in the Toba Batak language. The analysis employs a syntactic typology and functional construction approach, focusing on structural, morphological, and pragmatic strategies used by native speakers in daily communication. The data were collected through documentation and in-depth interviews with native speakers from the Samosir and Toba regions. The analysis was conducted using intralingual and distributional methods based on the theoretical framework of Sudaryanto (2015) and Payne (2006). The findings reveal that interrogative constructions in Toba Batak can be categorized into three main types: yes–no questions, partial questions, and rhetorical questions. Interrogative markers include particles such as ma, do, and na, as well as rising intonation patterns at the end of sentences. Additionally, word order inversion often occurs in partial interrogatives. Functionally, Toba Batak interrogatives are not limited to seeking information but also serve pragmatic purposes such as expressing requests, irony, or emotional emphasis. This research contributes to the linguistic documentation of local languages and provides valuable insight into Austronesian typology, especially in the grammatical description of regional languages in Indonesia. Keywords: Toba Batak language, interrogative sentences, linguistic typology, questionparticles, syntactic structure